Seminar Literasi Keuangan Mengenai Kebutuhan dan Investasi Melalui Kegiatan Talk Show Keuangan - Alpiansah, Restu; Stevany Hanalyna Dethan; Ika Yuliana; Putri Amalia Wardi; Baiq Nadia Nirwana (Yayasan Literasi Sains Indonesia, 2024)
Determining the priority scale of needs in daily life is often a problem for some people, especially the younger generation. Not infrequently, some people are often trapped by online loans which are definitely detrimental to the victims. This problem is caused by the low understanding of financial literacy. This community service was carried out using a discussion method packaged in the form of an open talk show which was attended by the society and more focused on young people, especially those with student status, numbering around 40 participants. This financial literacy discussion activity focuses on discussing financial topics about how someone can manage needs and investments. The output of this community service is increased public understanding regarding financial management to meet daily needs and investment needs. It is considered very important for the public society and the younger generation to have knowledge related to basic financial management so that they can be wiser in making financial decisions. This community service can be used as a forum or means to share basic financial knowledge related to investment and daily financial management to create financial stability.